CMI คอมพิวเตอร์ช่วยจัดการสอน กับ CAI คอมพิวเตอร์ช่วยสอน - สุกรี รอดโพธิ์ทอง (จุฬาลงกรณ์มหาวิทยาลัย, 1989)
The article defines the terms "computer-managed instruction" (CMI) and "computer-assisted instruction" (CAI) and describes their difference. The writer also details the elements and operations of CMI system, covering both hardware and software as recorded by Baker and Leiblum Flow charts depicting CMI and CAI processes are included.